Adverse effects of temperature on perinatal and pregnancy outcomes: methodological challenges and knowledge gaps - Mehta, Maitry; Basu, Rupa; Ghosh, Rakesh (Frontiers in Public Health, 2023)
Evidence linking temperature with adverse perinatal and pregnancy outcomes is emerging. We searched for literature published until January 30, 2023, in PubMed, Web of Science, and reference lists of articles focusing on the outcomes that were most studied like preterm birth, low birth weight, stillbirth, and hypertensive disorders of pregnancy. After examining the literature, we found important gaps in knowledge, and several methodological challenges. One important gap is the lack of knowledge of how core body temperature modulates under extreme ambient temperature exposures during pregnancy. We also do not know the magnitude of non-modulation of body temperature during pregnancy that is clinically significant, i.e., when the body starts triggering physiologic counterbalances. Furthermore, few studies are conducted in places where extreme temperature conditions are more frequently encountered, such as in South Asia and sub-Saharan Africa. Little is also known about specific cost-effective interventions that can be implemented in vulnerable communities to reduce adverse outcomes. As the threat of global warming looms large, effective interventions are critically necessary to mitigate its effects.